A Review of Different Text Categorization Techniques - Aggarwal, Anubhav; Singh, Jasmeet; Kapil Gupta, Dr (International Journal of Engineering and Technology, 2018)
In this paper, we focus on a major internet problem which is a huge amount of uncategorized text. We review existing techniques used for feature selection and categorization. After reviewing the existing literature, it was found that there exist some gaps in existing algorithms, one of which is a requirement of the labeled dataset for the training of the classifier.Â Â